Development of Arduino Uno-Based Free Fall Motion Props to Increase Learning Motivation Towards Practicum Results of 11th Grade Students - Firdaus, M. Arya; Subhan, Subhan; Arisandi, Nabila Dea; Zulkarnain, Zulkarnain; Hamzah, Hamzah; Sabaryati, Johri (Jurnal Educatio FKIP UNMA, 2024)
Research has been conducted on the development of Arduino Uno-based Free Fall Motion (FFM) teaching aids to increase learning motivation towards the results of practicum for 11th grade students of MAN 1 Mataram. This study aims, (1) to design arduino-based teaching aids on free fall motion (FFM) material, (2) to determine the validity level of teaching aids to 3 media experts and 3 material experts, (3) to determine the increase in student learning motivation, (4) to determine the results of student practicum, and (5) to determine the effect of learning motivation on student practicum results. This type of tool development is Research and Development (R&D). the subject model of this research is MAN 1 MATARAM students as many as 35 students. The instrument used was a questionnaire. The development model in this study uses a 3D model. 3D development model (ThreeD). This model is a modification of the Thiagarajan model which includes 4 stages called the 4D (Four-D) model. Based on the research objectives, a student's practicum teaching aid on GJB material was made. Based on the validity test results, the teaching aids are suitable for use as learning media in class 11 MAN 1 Mataram. Furthermore, the results of motivation based on the value before applying FFM props amounted to 51.60% (pretest). While the interpretation after the practicum (posttest) was 90.44% and the N-Gain was 0.46. This means that there are changes in learning activities in students. For the results of student practicum through the satisfaction interval with a very high category of 11 students, a high category of 23 students, a low category of 1 student and very low 0 students.  Meanwhile, the correlation of learning motivation to student practicum results shows rcount> table (0.450>0.344) and obtained tcount> table (2.895>2.035). From the truth value of the hypothesis it can be concluded that there is an influence between learning motivation (X) and practicum learning outcomes (Y) on GJB material.